2021
DOI: 10.3389/fpsyg.2021.734592
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Home Baby Euclid: Testing Infants’ Basic Shape Discrimination Online

Abstract: Online developmental psychology studies are still in their infancy, but their role is newly urgent in the light of the COVID-19 pandemic and the suspension of in-person research. Are online studies with infants a suitable stand-in for laboratory-based studies? Across two unmonitored online experiments using a change-detection looking-time paradigm with 96 7-month-old infants, we found that infants did not exhibit measurable sensitivities to the basic shape information that distinguishes between 2D geometric fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Finally, it should be noted that the results of the present study that used online testing, replicated for the most part those of our previous study that was conducted in the lab (Plastira & Avraamides, 2020 ), providing evidence that the online experiment platforms can be used effectively to conduct research on the perception of time. This was also supported by previous studies with adult samples that used different tasks, such as spatial memory tasks with static images (Segen et al, 2021 ), lexical decision tasks with reaction-time measurements (Hilbig, 2016 ), and preferential looking in children (Lo et al, 2021 ; but see Bochynska & Dillon, 2021 , for divergent findings). Notably, past studies reveal greater variability in the online responses compared with the laboratory ones, suggesting thus that larger samples should be used for online studies (see Segen et al, 2021 , for a discussion).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Finally, it should be noted that the results of the present study that used online testing, replicated for the most part those of our previous study that was conducted in the lab (Plastira & Avraamides, 2020 ), providing evidence that the online experiment platforms can be used effectively to conduct research on the perception of time. This was also supported by previous studies with adult samples that used different tasks, such as spatial memory tasks with static images (Segen et al, 2021 ), lexical decision tasks with reaction-time measurements (Hilbig, 2016 ), and preferential looking in children (Lo et al, 2021 ; but see Bochynska & Dillon, 2021 , for divergent findings). Notably, past studies reveal greater variability in the online responses compared with the laboratory ones, suggesting thus that larger samples should be used for online studies (see Segen et al, 2021 , for a discussion).…”
Section: Discussionsupporting
confidence: 76%
“…In addition to the above aims, as the experiments were conducted online, they also served the purpose of replicating earlier results of our research conducted in the lab, providing thus a test for the reliability of online testing for conducting timing research. Notably, while some past studies in other fields (e.g., Hilbig, 2016 ; Segen et al, 2021 ) have replicated with online testing patterns of results obtained in the lab, other studies (e.g., Bochynska & Dillon, 2021 ) did not.…”
mentioning
confidence: 92%
“…Previous studies aimed to answer that question by testing whether specific paradigms could be adapted to online settings (see review by Tsuji et al, 2022). For instance, Bochynska and Dillon (2021) did not successfully replicate findings from the lab. They conducted two asynchronous online experiments where they adapted the change-detection looking-time paradigm with infants aged 7 months.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that failure to discriminate between shapes might be due to distraction and infants having difficulties perceiving two distinct events when displayed on small compact screens of personal computers. Indeed, for this paradigm, most lab studies used two separate monitors or large projector screens (Bochynska & Dillon, 2021). On the other hand, Bánki et al's (2022) study successfully tested infants (aged 4-6 months) in an eye-tracking task that measures the detection of audio-visual asynchrony.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies were designed to collect data online with the aim of replicating the results of prior in-person studies. Most of these studies did yield successful replications (Leshin et al, 2021;Schidelko et al, 2021;Steffan et al, 2023;Vales et al, 2021), but some failed to replicate at least one result, citing task difficulty, parental involvement, computer screen size and quality and unfamiliarity with the online platform as contributing factors (Bochynska & Dillon, 2021;Smith-Flores et al, 2022). A meta-analysis found no difference between effect sizes of online or in-person developmental studies and no moderating effects of dependent measure type (looking or verbal) or method of online study (moderated or unmoderated) (Chuey et al, 2021).…”
mentioning
confidence: 99%